Genetic algorithm in material model parameters’ identification for low-cycle fatigue - Franulović, Marina; Basan, Robert; Prebil, Ivan (Computational materials science, 2009)
The material model presented in this paper describes elasto-plastic behaviour of the material under a cyclic load application. It takes into account damage occurrence and accumulation in the material and it’s relation to isotropic and kinematic hardening or softening. The material constitutive model for description of low-cycle fatigue behaviour is highly non-linear and therefore its parameter identification requires complex numerical procedure, such as genetic algorithm (GA). Because of its complexity, the unique genetic operators’ routines in GA calculation procedure are developed to make possible fast and reliable convergence to the results. These routines are incorporated in developed software solution. The calculation resulted in identification of material parameters that are validated in comparing material response of numerical solution with experimental data.